2019
DOI: 10.1155/2019/6095628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cytokine Release against Oral Mucosal Cell Line Culture (TR146) Stimulated by Neutrophil Elastase Associated with Behcet’s Disease

Abstract: Aim. Cytokines and chemokines may be involved in the onset of oral ulcer in Behcet’s disease. The aim of our study is to assess the cytotoxic effects of proinflammatory cytokines and chemokines on reconstructed oral mucosal cell line (TR146) when treated with different concentrations of neutrophil elastase (NE). Objective. For this purpose, a culture of the oral mucosal model (OMM) prepared from a cell line derived from an oral squamous cell carcinoma of buccal mucosa (TR146) is treated with different concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Soomro et al treated TR146 cells with neutrophil elastase, which is high in patients suffering from Behcet’s disease. They found that IL-8 and TNF-α levels were not affected and IL-1ß production was slightly increased [ 26 ]. Further studies showed that TNF-α induced IL-8 production already at concentrations starting at 10 ng/mL as well as CCL20, a Th17 chemokine in periodontal lesions [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soomro et al treated TR146 cells with neutrophil elastase, which is high in patients suffering from Behcet’s disease. They found that IL-8 and TNF-α levels were not affected and IL-1ß production was slightly increased [ 26 ]. Further studies showed that TNF-α induced IL-8 production already at concentrations starting at 10 ng/mL as well as CCL20, a Th17 chemokine in periodontal lesions [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In corroboration with the results of the present study, previous studies have demonstrated that the level of LDH is significantly higher in the H/R-induced I/R injury compared with the control in cardiomyocytes ( 33 35 ). The inflammatory factors TNF-α, IL-1β and IL-6 are commonly recognized as inflammatory indicators ( 36 ). TNF-α and IL-1β are responsible for the stimulation of chemokines and the secretion of adhesion molecules in ischemic tissues, and IL-6 is responsible for the regulation of inflammation ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%